Energy in a bathtub: Electricity trade between countries with different generation technologies - Finn R. Førsund (University of Oslo, Department of Economics, 2009)
Many countries have followed a policy of being self-sufficient in electricity. However, in the last two decades exchange of electricity across borders has become more widespread, and the European Union's policy is to encourage a gradual expansion of cross-border trading and integration of electricity markets. It is therefore of interest to study what happens with the price formation in home markets when borders are opened up for trade in electricity and generating technologies differ. There is a common international market, Nord Pool, between the Nordic countries since 1996, and trade now takes place between many European countries on a bilateral basis. A stylised general equilibrium model of trade of electricity between two countries; Hydro and Thermal, with hydro and thermal technologies, is used to investigate price and quantity consequences going from autarky to trade in a competitive market, as revealed by using a social planning perspective for cooperation between countries.
Keywords: F14; Q40; 330; Electricity; hydropower; thermal power; international trade; Stromhandel; Außenhandel; Wasserkraft; Wärmeenergie; Allgemeines Gleichgewicht; Theorie